EFFECT OF ORAL AND INJECTABLE CONTRACEPTIVES ON SERUM CALCIUM, MAGNESIUM AND PHOSPHORUS IN WOMEN - HAMEED, ABDUL; MAJEED, TASNEEM; RAUF, SHAHID; ASHRAF, MOHAMMAD; JALIL, M. ASIF; ULLAH, NASR; HUSSAN, ALTAF; NOREEN, ROOZEENA (Journal of Ayub Medical College Abbottabad, 2001)
Background: This study aims at evaluating serum calcium, magnesium and phosphorus levels in women taking oral and injectable contraceptives. Methods: Serum calcium, magnesium and phosphorus were measured in 50 women taking oral contra ptives (Lofeminal) and 50 women taking injectable contraceptive (Depo-medroxy progesterone acetate and Norigest). These women were used as controls before starting these contraceptives. Results: There was significant decrease in serum levels of calcium, magnesium and phosphorus in women taking oral contraceptives but there was significant increase in these minerals in women taking injectable contraceptives. Conclusions: It is suggested that these contraceptives should be used with due care and with proper investigations of the women before and during the therapy.